Dynamic modeling and simulation of a solar-assisted multi-effect distillation plant - de la Calle, Alberto; Bonilla, Javier; Roca, Lidia; Palenzuela, Patricia (Desalination, 2015)
This paper presents a dynamic model of a solar-assisted multi-effect distillation (MED) plant, carrying on with the previous work “Dynamic modeling and performance of the first cell of a multi-effect distillation plant” (de la Calle et al., 2014). The dynamic model has been designed according to the experience with an experimental solar thermal desalination system erected at CIEMAT-Plataforma Solar de Almería (PSA). The mathematical formulation based on physical principles describes the main heat and mass transfer phenomena in this kind of facilities. The model was implemented using the equation-based object-oriented Modelica modeling language. Based on a modular and hierarchical modeling, different specific-phenomenon submodels have been developed. They have been interconnected between them, thus making a three level deep hierarchy. All the submodels have been calibrated and validated with experimental data. The numerical predictions show a good agreement with measured data.
Keywords: Solar desalination; Falling film evaporation and condensation; Object-oriented modeling; Modelica